Microstructural stability of a nickel-based alloy overlay on a 2.25Cr1Mo steel substrate - Saghafifar, Hassan (2011)
Ni-based superalloy weld overlays are widely used in electricity generating plants to significantly reduce high temperature corrosion problems of ferritic steel components under service conditions. Welding a nickel alloy similar to IN625 onto the outer bore of a 2.25Cr1Mo steel tube enhances its service life as a superheater tube in the highly corrosive environment of a Waste-to-Energy boiler. For the purposes of studying the effects of high temperature service on the microstructure of this laid tube with a weld overly, a series of thermal exposure tests at 650˚C was performed for different times from 1 day up to 128 days. The microstructural evolution was studied using a combination of analytical techniques along with changes in hardness profile across the interface. Changes in the microstructure were examined using OM, SEM, EPMA, EBSD and FIB-STEM.